Foreign Policy of North Macedonia and Regional Security in the Balkans: Problems and Prospects - P. A. Smirnov (Управленческое консультирование)
The article focuses on identifying factors that inﬂuenced the foreign policy of the Macedonian state. In the ﬁrst years after the collapse of the socialistic Yugoslavia, most of the emerging countries, including Macedonia, deﬁned their development direction towards NATO and the EU, since the war in the Balkans required each republic to enter as soon as possible under the wing of a large international organization. On the way to the entry of North Macedonia into the EU and NATO, obstacles arose in the form of controversial issues in relations with neighbors. Thus, the foreign policy of the Macedonian state was designed to resolve conﬂicts with its neighbors, given the regional context. The settlement of local Balkan problems after 1999 contributed to some stabilization of the situation in the region. Achieving security in the Balkans has been and continues to be inextricably linked with the need for the region to join NATO, under whose auspices it is possible to create a collective security system. Moreover, the region faces new problems and challenges in the export of extremism from the Middle East and the socio-economic instability caused by the inﬂux of refugees from Syria.